Pengembangan Hutan Pinus Masyarakat Berbasis Kemitraan Sebagai Model Pemberdayaan Masyarakat Sekitar Hutan - Zainal Fanani R.; Hery Suliantoro (Jurnal Teknik Industri, 2010)
CV. Corning Sidoarjo is a home furnishings industry, one  product is kitchen furniture Pekalongan Regency is one regency in the region of Central Java Province has a forest area is relatively large, including public forests. Public forest for several years has been planted by pine trees, pine trees and even the population in the region has reached 400,000 trees. Suchlarge populations have not utilized optimally by the public, so the effort required to implement a development of that potential. One development that can be done is by processing the sap of pine into Gondorukem products, which Gondorukem is one of several types of raw materials industries, including batik industry is an important industrial sector in Pekalongan Regency. By doing this research is expected to be identified ways and strategies to develop the potential of public of pine forests and streng then the competitiveness of commodities produced Gondorukem, both on the regional market, national, and international. In addition, also to be identified new opportunities (in this case another potential can still be developed) and developing the competi tiveness of Pekalongan Regency through industrial products, such as batik and other industry related value chain. In an attempt to resolve the problem in this research, use industry cluster approach. This approach uses several instruments and data processing devices, including analysis of internal and external environment pine forest community, SWOT analysis, decision  making with Analitycal Network Process (ANP), analysis of the  competitiveness diamond approach and strategy formulation model taking into account some previous analysis and analysis supporters. Of some devices is expected to obtain an  appropriate strategy formulation and implementation of the development potential of the public pine forest in Pekalongan Regency in order to support increased competitiveness of  Pekalongan Regency.